Monetary Policy Transmission in the Eastern Caribbean Currency Union - Myrvoda, Alla.; Reynaud, Julien (Washington, D.C. : International Monetary Fund, 2018)
This paper empirically investigates international and domestic monetary policy transmission mechanisms in the Eastern Caribbean Currency Union (ECCU). We assess interest rate pass-through of both the U.S. policy rate and the ECCU minimum saving deposit rate (MSR) into domestic interest rates through the interest rate channel. While economic theory suggests that the international pass-through should be high in small open economies with fixed exchange rates and open capital accounts, our findings, based on regression analysis, point to a low long-run pass-through coefficient of the U.S. interest rate. The domestic transmission channel, however, is found to operate through changes in the MSR. The results hold for different interest rates (deposit and lending) and are supported by survey-based findings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet